Fluorescence and self-absorption free excitation spectroscopy of carbon monoxide isotopomers in the vacuum ultraviolet - De Bruyn, Andre (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017